Pengaruh Aktivasi Merek Melalui Instagram @Msglowbeauty Terhadap Keterlibatan Reseller Pada Produk MS.Glow - Sari, Deby Nur Winda (Universitas Negeri Surabaya, 2022)
The presence of social media brings benefits for beauty product businesses in implementing brand activation strategies. Brand activation is implemented through the use of content that can improve the relationship between brands and customers, so that companies are able to build partnerships by inviting loyal customers to become resellers. The owner of the MS.Glow brand also did the same thing through their Instagram account, namely @msglowbeauty, where the brand activation strategy that has been implemented accidentally creates reseller engagement on MS.Glow products. This study aims to examine the significant influence of brand activation through instagram @msglowbeauty on reseller engagement in MS.Glow products. Based on the concept of customer engagement, reseller engagement is defined as a process that involves cognitive, emotional and behavioral activities shown by a reseller through interactions with brands such as purchasing, using or reselling products. This research is included in the type of quantitative research with a survey method. The sampling technique used purposive sampling with a total of 100 respondents, who were identified as MS.Glow resellers in East Java. Based on the results of data analysis used Spearman Rank Correlation, the correlation coefficient value was 0.740 and a significance number was 0.000